Kursus Intensif Bahasa Arab Dewasa untuk Literasi Kitab Gundul: Analisis Dokumen Kurikulum LPBA Al-Ankabut Jambi - Kenyo Mitrajati; Randi Fidayanto (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study explains the importance of a nonformal Arabic language course model for adult learners who require functional competence in religious practice and everyday communication. It also examines how LPBA Al-Ankabut Jambi designs and operates a multichannel learning ecosystem while maintaining alignment across channels. Design/methods – A qualitative document analysis was conducted on program and level descriptions, thematic units, digital learning materials, including interactive audio-video slides, exercise and assignment guidelines, unit quiz designs, level project descriptions, and platform artifacts such as the LMS, website, and social media channels. These documents were thematically coded and interpreted through the IMTĀʾ framework to connect objectives, content, strategies, media, and assessment, without positioning the study as an institutional feasibility or quality audit. Findings – LPBA Al-Ankabut Jambi standardizes its content around the Al-ʿArabiyyah Bayna Yadayk series, adopts a communicative orientation with limited translation, and uses multimodal scaffolding to support comprehension. Assessment is organized into three layers: unit quizzes, mid-level and final-level examinations, and performance-based projects requiring integrated skills. However, the available artifacts do not provide standardized test-based outcome tracking or longitudinal evidence; therefore, the conclusions describe the design and operational logic rather than learning impact.